The prevalence of occupational stress among doctors in Kuala Lumpur Hospital in 1995-1996 - Ruhaini Ismail,; Noor Hassim Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study was conducted on 203 doctors serving in Kuala Lumpur Hospital under the Ministry of Health to determine the prevalence of occupational stress and the factors influencing it. Questionnaires were distributed to all doctors who are working at the said hospital. The questionnaires include personal data, 'The Medical Personnel Stress Scale' and 'Personal Stress Inventory' which were used to measure the factors as well as the occupational stress symptoms. The present study shows that the prevalence of occupational stress among doctors to be 40.4%. Significant associations were found between occupational stress and job categories, age-groups, sex, length of service and monthly income (p<0.05). The prevalence of occupational stress is highest among the Housemen (65.2%), followed by the Medical Officers (41.9%). The specialists formed the group least affected by occupational stress (30.7%). Those who were 30 years and younger experienced the highest level of occupational stress (53.8%) as compared to those who are above 30 years of age (31.7% ). Other characteristics such as marital status, number of children and race have no effect on the prevalence of occupational stress and the associations were found not to be significant (p>O.05). Apart from that, the prevalence of occupational stress between the different units is also not significant (p>O.05). Therefore, it can be shown in this study that for every 3 doctors, 1 will be under stress. This situation is worse among the Housemen, whereby for every 3 doctors, 2 will be under stress. Hence, it can be concluded that doctors are actually at high risk of getting occupational stress and as such, the relevant authorities should identify and take proper actions to overcome this problem.